Susa and Elam : archaeological, philological, historical and geographical perspectives : proceedings of the international congress held at Ghent University, December 14-17, 2009 - Graef, Katrien de.; Tavernier, J. (Mémoires de la Délégation en Perse, 2012)
In December 2009, an international congress was held at Ghent University in order to investigate, exactly 20 years after the 36th RAI "Mésopotamie et Elam", the present state of our knowledge of the Elamite and Susean society from archaeological, philological, historical and geographical points of view. The multidisciplinary character of this congress illustrates the present state of research in the socio-economic, historical and political developments of the Suso-Elamite region from prehistoric times until the great Persian Empire. Because of its strategically important location between the Mesopotamian alluvial plain and the Iranian highlands and its particular interest as point of contact between civilizations, Susa and Elam were of utmost importance for the history of the ancient Near East in general.